An eco-solution for track and trace of goods and third party logistics - West, Martin; Chang, Elizabeth; Armstrong, B.; Roos, K. (IEEE, 2005)
This paper presents a new economic costeffective solution known as web and telephony based method for tracking and tracing of goods and small and medium sized third party logistic providers. Considering that these companies usually operate on very flat margins, a comparison is made of the available track and trace technologies like GPS, Mobile Phone Approximately GPS and Java based cell tracking in terms of costs, operating risks, and other evaluation criteria.